Relationships of plankton content in the digestive tract of a red tilapia (Oreochromis sp.) to the accumulation of lead (Pb) into the fish muscle in the old lake of post-tin mining of Bangka Belitung - Robin Robin; Kukuh Nirmala (Journal of Aquatropica Asia, 2016)
The red tilapia were cultivated in kolong (above 30 years age of lake of post-tin mining) for four month; on the rate of lead (Pb) biomagnification in the organs (liver, kidney and muscle), given positif correlation from planktons in instestine composition, and its effects to the growth rate has been investigated. Results revealed that in the third month, accumulation of lead in the organs of both species were increased, especially in their livers, above the safe level to be consumed (62.14 mg/kg, 8.41 mg/kg and 15.39 mg/kg, 55.23 mg/kg, respectively), but then were decreased in the fourth month. Biomagnification of lead affects the growth rate of both species significantly